HUBUNGAN FAKTOR LINGKUNGAN DAN INDIVIDU DENGAN GEJALA PENYAKIT DERMATITIS KONTAK DI KAMPUNG PEMULUNG, JURANG MANGU TIMUR, TANGERANG SELATAN TAHUN 2023 - Helena Diah Habibah, (2023)
Contact dermatitis is a skin disease in the form of inflammation and is caused by materials or substances that are attached to the skin which can have an impact on the appearance of physical, social and psychological problems. The main objective of this study was to determine the environmental and individual factors associated with symptoms of contact dermatitis in Pemulung Village, Jurang Mangu Timur, South Tangerang in 2023. Scavengers are synonymous with direct contact in dirty environments and have minimal behavior in maintaining cleanliness. while environmental and individual factors can increase the risk of exposure to contact dermatitis in a person. This research uses a cross-sectional study design using quantitative methods, by examining scavengers who live in Kampung Pemulung Jurang Mangu Timur with a sample size of 110 using Lemeshow calculations of two proportions and samples taken by accidental sampling. Primary data is generated through the use of questionnaires which are filled out through interviews and direct observation with respondents. The results of the study revealed that 65.5% of scavengers had symptoms of contact dermatitis. Related factors include low level of knowledge (p-value = 0.045), occupancy density does not meet the requirements (p-value = 0.000), poor personal hygiene (p-value = 0.000), and incomplete use of PPE (p-value = 0.020) with the most influencing factor being the incomplete use of work PPE. It is suggested that to prevent scavengers from developing dermatitis, there needs to be an increase in knowledge, personal hygiene, and complete PPE.